FEATURES OF KNEE JOINT ENDOPROSTHESIS FOR PATIENTS WITH RHEUMATOID ARTHRITIS - Xo’janazarov Ilxom Eshqulovich; Axmedov Xalmurad Sa’dullayevich; Anorboyev Ma’ruf Xolbo’ta o’g’li (Scholar Express Journals, 2024)
Rheumatoid arthritis (RA) is a disease that belongs to the group of systemic autoimmune diseases of connective tissue. One of its main manifestations is an erosive-destructive lesion of the surface of the joint.
Keywords: Rheumatoid arthritis; surface; group; connective